THE IMPLEMENTATION OF RADEC (READ, ANSWER, DISCUSSION, EXPLAIN, CREATING) STRATEGY IN TEACHING ENGLISH VOCABULARY MASTERY AT SD NEGERI PATOMPO II MAKASSAR - Ningsih, Eva Yulia; Sakkir, Geminastiti; Aeni, Nur (State University of Makassar, 2022)
The objective of this research was to find the effect of the RADEC strategy in teaching English vocabulary mastery in class VI SD Negeri Patompo II Makassar. This study was a pre- experimental design with one group given the RADEC strategy. The population of this research were all students of SD Negeri Patompo II Makassar. The population of this research used purposive sampling technique. The sample consists of 15 students. Data were collected using tests (pretest and posttest). The data collection technique used SPSS version 28. The results of descriptive statistical analysis showed that the mean pretest result was 56.13 in the “poor” classification. The mean posttest result was 85.86 in the “good” classification. Therefore, it can be concluded that the RADEC strategy effect in teaching English vocabulary mastery at SD Negeri Patompo II Makassar. Keywords— RADEC Strategy, Vocabulary Mastery